The timing of deep brain stimulation for Parkinson disease in the UK from 1997 to 2012. (15th September 2015) - deSouza, R. M.; Akram, H.; Low, H. L.; Green, A. L.; Ashkan, K.; Schapira, A. H. V.
Abstract : Background and purpose: Deep brain stimulation (DBS) for Parkinson disease (PD) has traditionally been reserved for the late stages of the disease. There is evidence that DBS is also effective if applied earlier in the disease course. Changes in the frequency of DBS procedures in the UK over a 15‐year period were investigated. Methods: A retrospective review was performed of patient age and disease duration for DBS surgery for PD in UK neurosurgical units from 1997 to 2012 using departmental databases. Results: The number of DBS procedures in the UK increased from three in 1997 to over 80 per year during this period. The mean age at the time of surgery (60 years) and the mean duration of PD at the time of DBS (11 years) remained unchanged over 15 years. Conclusions: The age and disease duration at which DBS is performed for PD in the UK has been static over a 15‐year period and DBS appears to remain a therapy for PD applied late in its course. This may change in the light of clinical evidence suggesting a benefit for earlier DBS.